Potensi Wisata Pesisir dengan Peningkatan Atraksi Wisata berbasis Sumberdaya Perairan Berkelanjutan - Adibrata, Sudirman; Umroh, Umroh; Franto, Franto; Fatimah, Siti (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Developing tourist attractions can encourage increased community participation in managing tourist destinations, especially those based on water resource potential. Local or domestic tourists are the backbone of most tourism destinations. Therefore, challenges, opportunities, and innovation in optimizing the potential of aquatic resources require sharing information based on experience in several regions. The research aims to assess the potential for sustainable water resource-based tourist attractions. This research was conducted from March 2022 to August 2023 in 9 districts/cities with tourist destinations. The method uses qualitative methods through field observations and literature studies. The results show that coastal tourism management must consider tourist attractions, carrying capacity, infrastructure, facilities, and services. Tourist attractions can motivate tourists to visit. Tourists find out about tourist destinations usually based on information from the internet, from friends/relatives, and social media. Clean water facilities at tourist locations are essential, especially during peak season. The sources of income for tourism managers comes from entrance tickets to tourist locations, sponsorships, and rides. The mode of transportation for domestic tourists is dominated by cars and motorbikes. Some examples of tourist attractions visited include tourism educational activities such as salt making, mangrove crab rearing of apartment system, fishing, culinary, sponsorship, lodging, swimming pools, fish therapy, photo boats, viewing panoramic views of beaches, mangroves, swimming, snorkeling and diving on coral reefs. Tourist destinations provide economic benefits and sources of income. Sustainable tourism promotes economic growth, social inclusion, environmental protection, and tourism governance.